Institutional reforms in Indian irrigation - Gulati, Ashok, 1954- (SAGE Publications, 2005)
As water resources become increasingly scarce in India and demand only increases, the challenge of sustaining irrigation systems and the lands they serve is a matter of crucial importance. In particular, the livelihood of millions of farmers is threatened. India's canal irrigation systems, which have so far made an enormous contribution to food security, are now in crisis because of increasing competition for water, poor management, and declining funding. The authors of this book examine the nature of large-scale surface irrigation systems in India, analyze their associated problems, and discu.